Friedmann-Lemaitre-Robertson-Walker braneworlds - Silva, P. Michel L. T. da [UNESP]; Souza Dutra, A. de [UNESP]; Hoff da Silva, J. M. [UNESP] (Elsevier B.V., 2017)
We study the cosmological evolution with nonsingular branes generated by a bulk scalar field coupled to gravity. The specific setup investigated leads to branes with a time-dependent warp factor. We calculate the effective Hubble parameter and the effective scale factor for the FLRW branes obtained solutions. The spatially dependent branes solutions also were found. (c) 2017 The Authors. Published by Elsevier B.V.